In Vitro Activity of Geldanamycin Derivatives against Schistosoma japonicum and Brugia malayi - David Wenkert; Bernadette Ramirez; Yuehai Shen; Michael A. Kron (Journal of Parasitology Research)
Geldanamycin (GA) is a benzoquinone-containing ansamycin that inhibits heat shock protein 90. GA derivatives are being evaluated as anti-neoplastic agents, but their utility against parasites whose heat shock proteins (Hsps) have homology with human Hsp90 is unknown. The activities of four synthetic GA derivatives were tested in vitro using adult Brugia malayi and Schistosoma japonicum. Two of the derivatives, 17-N-allyl-17-demethoxygeldanamycin (17-AAG) and 17-N-(2-dimethylaminoethylamino)-17-demethoxygeldanamycin (DMAG), are currently in human clinical trials as anticancer drugs. Using concentrations considered safe peak plasma concentrations for these two derivatives, all four derivatives were active against both parasites. The less toxic derivative 17-AAG was as effective as GA in killing S. japonicum, and both DMAG and 5′-bromogeldanoxazinone were more active than 17-AAG against B. malayi. This work supports continued evaluation of ansamycin derivatives as broad spectrum antiparasitic agents.